(untitled) (Foro de Educacion, 2024)
This article analyses the economic policy in Spain during the govern- ments of the Spanish political transition from 1975 to 1986. It considers the different areas of economic policy with special emphasis on the development of welfare state issues in this period. Taking into account the difficult economic and political situation in 1975, there were some important advances in social policy and progressive taxation during the period. The transition to democracy in Spain changed the role and size of the public sector above all from 1975 to 1986. The social demands over the political system were possible improvements in the progressive and redistributive policies in education, health, and social programs. Spain’s transition to democracy and the first period of welfare state show a mutually reinforcing and its consequences were the modernization of the Spanish economy. However, from 1986 the economic develop- ment and the progress of welfare state have had a different growth.